Educação matemática e formação do técnico agrícola: entre o “aprender pela pesquisa” e o “aprender a fazer fazendo” - Toledo, Neila de Toledo e (Universidade do Vale do Rio dos Sinos, 2017)
The general objective of this thesis is to discuss the agricultural technician education at IFRSSertão, particularly in terms of mathematical education. The study has been theoretically supported by Michel Foucault and his commentators’ contributions. The research material consists of interviews with graduates that attended Sertão Federal Agro-technical School in the 1980s and just-graduated students of the Federal Institute of Education, Science and Technology of Rio Grande do Sul – Sertão Campus, as well as institutional documents – current pedagogical project and pedagogical plan used in the 1980s – and school material from both periods. The analysis of this material (performed from the perspective of Foucauldian discourse analysis and by means of the storytelling approach) has led to the following conclusions: a) the agricultural technician education at IFRS-Sertão is currently guided by the pedagogical principle of “learning through research” and is aligned with the neoliberal logic, which is marked by competitiveness, individualism and entrepreneurship; b) the principle of “learning through research” is associated with the biotechnological logic. This has put at stake the use of scientific procedures based on the vegetal biotechnological area, such as the research on the use of transgenic seeds (genetically modified organisms – GMOs) produced by the X company; c) the pedagogical practices linked to vegetal biotechnology have acted on the school subjects by subjectivating them to adhere to the GMO discourse; d) the principle of “learning through research” has caused the school subjects to understand that continuing study is a condition for them to be included in the labor market and continue to work as agricultural technicians; e) the pedagogical principle of “learning by doing”, which was in force along the 1980s, aimed at the appropriation of scientific knowledge to improve the students’ previous experiences; f) the displacement from the principle of “learning by doing” to the principle of “learning through research” has caused a change of emphasis aiming at qualifying students’ experiences through the Scientific Method; g) over the last three decades, the list of contents of Mathematics has not changed, the mathematical education in Mathematics has maintained its abstract, formal approach, and mathematical education in technical disciplines has been aligned with the technoscientific discourse, including technological resources; h) the mathematical education discourse that is currently in operation in the Agricultural Technician course at IFRS-Sertão can be regarded as one of the vectors (but not the only one) that constitute the technoscientificity.
Keywords: Educação matemática; Formação do técnico agrícola; Modernização do campo; Tecnociência; Governamentalidade; Mathematical education; Agricultural technician education; Agricultural modernization; Technoscience; Governmentality; ACCNPQ::Ciências Humanas::Educação